PENERAPAN MEDIA WORDWALL PADA PEMBELAJARAN IPA MATERI CIRI-CIRI MAKHLUK HIDUP UPTD SD NEGERI 7 SIMPANG MAMPLAM KECAMATAN SIMPANG MAMPLAM KABUPATEN BIREUEN: Penerapan Media Wordwall Pada Pembelajaran IPA Materi Ciri-Ciri Makhluk Hidup UPTD SD Negeri 7 Simpang Mamplam, Kabupaten Bireuen - Syarfida; Sarwati; Mulyana; Ridwan; Afkar (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2025)
Observations at UPTD SD Negeri 7 Simpang Mamplam, Bireuen Regency, revealed that more than half (50%) of the students struggled to correctly answer questions regarding the lesson material on the characteristics of living things. To address this issue, a Community Service (PKM) activity was conducted using Wordwall as an interactive learning tool. The activity involved 21 fifth-grade students over the course of one week. The results of the training and implementation demonstrated an increase in student engagement and learning motivation; the average learning activity score rose from 79.36% in the first session to 85.07% in the third session. Furthermore, the involvement of teachers and parents in the learning process increased, with 80% of parents reporting that they were more actively supporting their children's learning at home. Consequently, the outcomes of this community service initiative are expected to serve as a reference for fostering enjoyable and beneficial learning activities within the school environment.